Gold catalysis: highly functionalized cyclopentadienes prepared by intermolecular cyclization of ynamides and propargylic carboxylates - Rettenmeier, Eva; Schuster, Andreas M.; Rudolph, Matthias; Rominger, Frank; Gade, Christoph A.; Hashmi, A. Stephen K. (Angewandte Chemie. International edition, 2013)
When an ynamide meets a gold carbenoid: Highly electrophilic gold carbenoids available from propargylic esters by means of 1,2-acyloxy migration open up new reaction pathways for ynamide gold chemistry. In this way highly functionalized cyclopentadiene derivatives become accessible (see scheme; EWG=electron-withdrawing group).
Gesehen am 03.01.2022